Raman Spectrum Online Monitoring in Aspirin Synthesis Process - Su, Hui; Sun, Kuo; Yao*, Zhixiang; Huang, Peixian; Liu, Liu (Asian Journal of Chemistry, 2014)
In this work, the Raman spectra were obtained directly in the synthesis process of aspirin as prediction set. The concentration sample according to the amount of material changes before and after reaction and it’s extracted Raman information made up training set and a quantitative analysis model of the salicylic acid-acetic anhydride-aspirin mixed system was established by applying partial least squares (PLS). The values of correlation coefficient squared between measured and regression (R2), root mean square error of prediction set (RMSEP), mean deviation (MD) indicate that the influence of the prediction precision by the baseline drift can be effectively reduced in the method of spectrum pretreatment via mormalize + savitzky-go1ay smoothing first derivative. After the prediction set was used in this analysis mode, the mass per cent between salicylic acid and aspirin of online monitoring was 4.59 %, while the off-line Raman analysis and high performance liquid chromatography analysis results were 5.66 and 2.75 %. The relative deviations were -1.07 and 1.84 %. This method provides effective data support for synthesis of aspirin Raman spectroscopy online monitoring.